RESPON PENGUSAHA TENTANG FITUR QRIS SEBAGAI MEDIA TRANSAKSI DALAM PERSPEKTIF KEUANGAN SYARIAH DI KOTA WATAMPONE - Aqil Fajrul; Kamiruddin Kamiruddin; Muh Hasbi Ash Shiddiq (Institut Agama Islam K.H. Sufyan Tsauri, 2024)
The purpose of this research is to determine the response of entrepreneurs in Watampone City towards the QRIS feature as a transaction medium and analyzing QRIS features as a transaction medium from the perspective of islamic finance in Watampone City. This research uses a qualitative approach, with data collection techniques namely observation and interviews. The data analysis techniques used are data reduction, data condensation, and drawing conclusions. The results of the study show that 1) The response of entrepreneurs in the city of Watampone to the QRIS feature as a transaction medium shows a positive response to the QRIS feature because it provides ease of transactions, efficiency, and opportunities to develop a more modern business. 2) The QRIS feature as a transaction medium in Watampone City meets the main principles in Islamic finance, namely the prohibition of usury, transparency, and prevention of double payments. This provides an efficient and Sharia-compliant transaction solution, so it can be accepted and used by entrepreneurs in carrying out their economic activities.